Preconcentration of Mercury in Water Samples by Cloud Point Extraction and its Determination by Electrothermal Atomic Absorption Spectrometry - Dehghani Mohammad Abadi, M.; Chamsaz, M.; Arbab-Zavar, M.H.; Taheri, S.A. (Asian Journal of Chemistry, 2012)
A pre-concentration and determination methodology for mercury at trace levels in water samples was developed. Cloud point extraction was successfully employed for pre-concentration of mercury prior to electrothermal atomic absorption spectrometry (ETAAS) using Triton-X-100 as surfactant. In this study the effect of different modifiers on mercury determination were also investigated. Under the optimum conditions, the limit of detection (LOD) was 1.2 μg L-1. RSD for 10 replicate determinations of 10 μg L-1 Hg was 4.7 %. The calibration graph was linear in the range of 10-100 μg L-1 with a correlation coefficient of 0.997. The method was successfully applied to determine mercury in sea water samples.